Quasi-position vector curves in Galilean 4-space - Elsharkawy, Ayman; Elsharkawy, Noha (Frontiers in Physics, 2024)
The Frenet frame is not suitable for describing the behavior of the curve in the Galilean space since it is not defined everywhere. In this study, an alternative frame the so-called quasi-frame is investigated in Galilean 4-space. Further, the quasi formulas in Galilean 4 space are deduced. Moreover, the quasi curvatures are obtained in terms of the quasi frame and its derivatives. quasi-rectifying, quasi-normal, and quasi-osculating curves are studied in Galilean 4-space. We prove that there is no quasi-normal and accordingly normal curve in Galilean 4-space.